Women and Leadership in Higher Education: Faculty Members’ Voices in Jambi - Sari, Siti Rahma; Harja, Harlina; Hidayati, Sri (IJER (Indonesian Journal of Educational Research), 2023)
Gender equity in the higher education context is a crucial issue. This study aims at investigating the issue of women and leadership in higher education. Further, this study explores factors impacting their efforts to take up the administrative positions and become university leaders. In this study, a qualitative design with a case study approach was employed to investigate the research questions. Data were collected through semi-structured in depth-interview with ten faculty members from four higher educational institutions in Jambi Province. All interviews were audio taped and transcribed for coding by using a constant comparative analysis method to identify the key themes. The data highlight the absence of women in higher education management due to personal problems, participation rates are still low and reflect in equalities in terms of women, and the representation of women in senior level position in higher education is still scarce. Majority of participants expressed that they are ready to receive opportunities for administrative positions. Further, the findings of this study also indicate that the opportunity for women to become university leaders is widely opened, but commonly they find various barriers to take up senior leadership. Recommendations to promote the readiness of women to take up senior leadership are discussed.